Accuracy in determining kinetic parameters with force plates embedded under soil-filled baseball mound - Yanai, T.; Matsuo, A.; Maeda, A.; Nakamoto, H.; Mizutani, M.; Kanehisa, H.; Fukunaga, T. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
We developed a force measurement system embedded in a soil-filled mound for measuring ground reaction forces (GRF) acting on baseball pitchers and examined the accuracy of determining the point of force application (PFA) and kinetic parameters computed from GRF. Three 1.0 x 0.9 m2 force platforms were placed on the concrete foundation of an indoor sports facility and three bays were fixed onto the aluminum plates of the force plateorms. In each tray, clay-blocks were laid tightly and a mixture of red sand and volcanic-ash was used to make a smooth surface layer. The mean absolute error was 6.0 f 4.0 mm in determining PFA, less than 15.5 Ns (5% of the true value) in determining linear impulse. These results suggest that the present method is valid for measuring the PFA and GRF acting on the pitcher's legs for analyzing kinetics of pitching performances.